Axially chiral propeller-shaped spiroborates with aggregation-modulated circularly polarized luminescence. (September 2021) - Duan, Wenzeng; Li, Kang; Ji, Honghan; Huo, Yanmin; Yao, Qingxia; Liu, Houting; Gong, Shuwen
Abstract: Modulating CPL with large luminescent dissymmetry factors and reversal signals is a great challenge in developing chiroptical small organic molecules (SOMs) materials. We herein report a series of axially chiral propeller-shaped pyridyl-/benzothiazolyl-enolato-naphtholate spiroborates (( R ) -/ ( S )-2a -2d ). Of these spiroborates, the CPL signals of ( R ) -/ ( S )-2c -2d could be effectively modulated by increasing water fraction ( f w ) from 50% to 90% in the THF-H2 O solution. ( R ) -/ ( S )-2c exhibit aggregation-amplified CPL with the dissymmetry factor ( g lum ) up to 2.38 × 10 −2 and ( R ) -/ ( S )-2d show aggregation-induced CPL. In addition, the CPL signals of ( R ) -/ ( S )-2c exhibit reversible inversion with the f w increasing from 50% to 90%. The amplification and inversion of the CPL signals are revealed via the helical self-assemblies observed by scanning electron microscopy (SEM) images and the promotion of the population of emissive intramolecular charge transfer (ICT) state. Graphical abstract: Aggregation-amplified CPL and aggregation-inverted CPL with dissymmetry factor ( g lum ) up to 2.38 × 10 −2 were reported based on axially chiral propeller-shaped spiroborates. Image 1 Highlights: Axially chiral propeller-shaped spiroborates were facile synthesized. 2c exhibits aggregation-amplified CPL with g lum up to 2.38 ×10 -2 and 2d shows aggregation-induced CPL. The CPL signals of ( R ) -/ ( S )-2c exhibit reversible inversion with the f w increasing from 50% to 90%.